Semiotic Analysis on Sprite Advertisement (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2026)
The analysis of this research is to find out the meaning of icons and symbols in Sprite poster advertisement and explains their semiotic process. The semiotic analysis method is used to identify and analyze the data which focus on representament, object, and interpretant by using the triadic semiotic by Pierce’s theory. This research applied a descriptive qualitative analysis method. The study reveals that the advertisements using the semiotic process of triadic method by using Pierce’s theory. The study reveals that the icons (pictures), symbols (written language) and interpretant from the poster advertisement. The data are taken from Google. Besides, the finds that the icon on the advertisement can be the first aspect that can give direction to the meaning.The study shows that the semiotic process from in the three data of Sprite advertisements 3 icons, 4 symbols, and 3 objects. From this analysis it can be deduced that advertisements have different meanings and different interpretations.